PERSEPSI MAHASISWA TERHADAP PELAYANAN PERPUSTAKAAN UNIVERSITAS TRUNOJOYO MADURA - Fitri Jayanti; Nanda Tika Arista (Kompetensi (Competence : Journal of Management Studies), 2018)
ABSTRACTCollege Library is one of the main supporting units in the effort to realize the vision and mission of a higher education activity. Based on these conditions, the role of the library is very dominant in order to foster insight into students as prospective graduates and competency of lecturers in order to carry out the Tri Dharma of Higher Education since the library is the heart of Higher Education. This research has described that, students' perception of Trunojoyo Madura University library services includes aspects of service personnel, aspects of facilities and infrastructure (completeness of library material collections, buildings / spaces, other supporting facilities), social conditions of the library's social environment (visitor interaction with library staff and between library visitors) and the security and comfort of the environment is "good". While the factors that influence the low quantity and quality of student visits to the Trunojoyo Madura University Library are in principle more caused by factors of lack of interest in reading students, the existence of other libraries scattered in each regional faculty and library, the availability of reading materials in bookstores , there are no regulations that require students to visit (academic prerequisites). Based on these conditions it is expected that in the future the Trunojoyo Madura University Library can become an international library 'through serious attention in better development efforts so that the vision and mission of the Trunojoyo Madura University can truly be realized.